1186. Cefazolin inoculum effect predicts reduced susceptibility to other antibiotics and patient outcomes in MSSA endovascular infections. (31st December 2020) - Smelter, Dan; McCrone, Sue; Rose, Warren
Abstract: Background: MSSA Infective endocarditis (IE) is inherently a high-burden infection with up to a 30% mortality rate. Cefazolin is an appealing treatment option for IE with low toxicity and a favorable dosing scheme. However, cefazolin has been associated with treatment failure in IE, attributed to an inoculum effect. The specific mechanism underlying the cefazolin inoculum effect (CIE) remains undetermined, but CIE has been linked to both blaZ expression and agr dysfunction. This study aims to determine whether CIE is linked to reduced susceptibility to other antibiotics and worse outcomes regardless of therapy in MSSA endovascular infections. Methods: Sixty-four MSSA strains were collected from patients with endovascular infections not treated with cefazolin. To determine CIE phenotype, strains were cultured and MICs assayed for cefazolin, nafcillin, and vancomycin at 10 7 CFU/mL for high-inocula (HI) and 10 5 CFU/mL for standard-inocula (SI). This study defined CIE as a ≥ 4-fold increase in MIC at HI compared to SI, with at least an MIC of 4 mg/L at HI. Nitrocefin disks identified blaZ expression, and beta lysin disks were used to determine hemolysin type and agr function. Patient outcomes of mortality and bacteremia duration were assessed across cohorts. Results: Twenty-four strains exhibit a CIE (38%), with 10 strains having an MIC of ≥ 32mg/L at HI. Nafcillin and vancomycin also had an inoculum effect, uncoupled from the CIE and occurring at a lower frequency and amplitude at HI. Presence of CIE had a greater association with blaZ expression (71% vs 25%) than agr dysfunction (38% vs 20%). 50% (9/18) of CIE infections were cleared within 48 hours while 77% (20/26) of CIE-negative infections were cleared within 48 hours ( P =0.106). However, presence of CIE was not associated with increased mortality (25% CIE-positive vs 35%; P =0.578) Conclusion: Previous studies for CIE failed to enrich for isolates from endovascular sources, where inocula are known to be high. This study presents one of the largest endovascular source cohorts for CIE evaluation. It identifies that CIE prevalence (38%) is higher than reports from diverse infection sources (10-36%). CIE appears to predict bacteremia duration with other MSSA treatment options, suggesting mechanisms independent of blaZ and agr function for this phenomenon. Disclosures: Warren Rose, PharmD, MPH, Merck (Grant/Research Support)Paratek (Grant/Research Support)